ISLAMIC HYPNOTHERAPY TO REDUCE PARENT'S ANXIETY TOWARDS THE FUTURE OF CHILDREN WITH AUTISTIC SPECTRUM DISORDERS - Tri Winarsih; Zahro Varisna Rohmadani (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
Parents of children with autism spectrum disorder (ASD) have anxiety about their children's future. This anxiety affects the psychological well-being of parents. Therefore, parents need advice to reduce their stress level. Hypnotherapy methods have been proven that those are able to reduce anxiety in various cases. For this reason, this study aims to determine the effectiveness of Islamic hypnotherapy in overcoming the fear of parents with ASD children. This study employs a pre-experimental method consisting of one group which takes treatment with the Islamic hypnotherapy method. The measurement of anxiety about the child's future was conducted by giving a scale of stress to child's future, before and after providing an intervention.The results were tested by using SPSS with Wilcoxon Signed Rank Test Z = -2.251 and Asymp. Sig. (2-tailed) = 0.024 (p<0.05), which mean that Islamic hypnotherapy can reduce the anxiety faced by parents who have autism children. Islamic hypnotherapy is capable of reducing stress because it teaches positive suggestions and and releases samples’ emotions.